PREFERENSI RUANG-RUANG BERSOSIALIASI URBAN KOTA MEDAN (STUDY KASUS KAWASAN KOTA MATSUM, MEDAN, SUMATERA UTARA) - Sabam Syahputra Manurung (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2022)
The preference for gathering spaces for urbanites has shifted since the 2000s, the trend of gathering activities of young people who initially in public spaces, such as parks, terraces, and private spaces, began to shift towards activities in spaces that offer the charm of hedonism and simple. As a result, a new habit arises, namely a habit of buying and hanging-out in the economic area of the city, both in the form of cafés, food stalls, and other gathering places that are hedonistic in nature. This study used an observation approach at three locations in the Matsum City Area, in addition to observations conducted as well as interviews with respondents, and then conducted an analysis of the preferences of social spaces between two groups of actors who had different backgrounds, but achieved the same goal. The results of this study show that the creation of social space preferences from the activities and relations of fellow young people and the relationship of young people with traders has formed social value activities, and has produced economic value around the city of Matsum.